Development of Learning Materials Based on Higher Order Thinking Skills (HOTS) in The Makeup Room Decoration Course - Sitompul, Astrid; Wahidah, Siti; Lubis, Habibah Hanim; Fauzani, Asrah Rezki (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The 21st century learning paradigm emphasizes the development of Higher Order Thinking Skills (HOTS) to prepare learners with essential competencies such as critical thinking, problem-solving, decision-making, and creativity. This study developed HOTS-based learning materials for the Makeup Room Decoration course using the Problem-Based Learning (PBL) model with a Case Method (CM) and the Project-Based Learning (PjBL) model with a Team-Based Project (TBP) approach. The research employed Thiagarajan’s 4-D model, consisting of four stages: define, design, develop, and disseminate. The developed products included a Semester Learning Plan (RPS), an e-book with video tutorials, and a HOTS test instrument. The research trials were conducted in three stages-expert validation, limited trials, and field trials-involving experts, lecturers, and students. Data were collected using observation sheets, validation forms, assessment questionnaires, and tests. The results indicated that the developed learning materials met the criteria for validity, practicality, and effectiveness. The RPS was categorized as highly valid (Aiken’s V = 0.8375), the e-book as moderately valid (V = 0.723 by learning design experts and V = 0.823 by media experts), and the HOTS test instrument as highly valid (V = 0.937). The limited trials showed that the materials were very practical, while field trials demonstrated effectiveness with an average student achievement rate of 81.7%. These findings confirm that the developed learning materials are feasible and effective in enhancing students’ higher-order thinking skills in the Makeup Room Decoration course of the Beauty Education Program at the State University of Medan.